2020
DOI: 10.3390/nu12071963
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Vitamin C Status and Prevalence of Deficiency: A Global Health Perspective

Abstract: A recent review of global vitamin C status has indicated a high prevalence of deficiency, particularly in low- and middle-income countries, as well as in specific subgroups within high-income countries. Here, we provide a narrative review of potential factors influencing vitamin C status globally. The in vivo status of vitamin C is primarily affected by dietary intake and supplement use, with those who supplement having a higher mean status and a lower prevalence of deficiency. Dietary intake can be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 116 publications
2
109
0
1
Order By: Relevance
“…Research has indicated that the bioavailability of vitamin C from supplements is comparable to that from fruit and vegetables [ 91 ], although the latter is encouraged due to the presence of other essential nutrients and health-promoting phytochemicals. However, it is not always possible for people to obtain sufficient vitamin C through diet alone, particularly in light of the low vitamin C content of many staple foods [ 76 ]. Therefore, additional supplementation is encouraged in these situations, particularly if there are also underlying morbidities or other risk factors that increase the requirement for the vitamin [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that the bioavailability of vitamin C from supplements is comparable to that from fruit and vegetables [ 91 ], although the latter is encouraged due to the presence of other essential nutrients and health-promoting phytochemicals. However, it is not always possible for people to obtain sufficient vitamin C through diet alone, particularly in light of the low vitamin C content of many staple foods [ 76 ]. Therefore, additional supplementation is encouraged in these situations, particularly if there are also underlying morbidities or other risk factors that increase the requirement for the vitamin [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous factors that affect vitamin C status and requirements, including health aspects such as obesity; these have been covered in detail in other recent reviews [ 10 , 76 ]. Low vitamin C status is thought to be both a cause and a consequence of various communicable and non-communicable diseases.…”
Section: Associations Between Vitamin C Status and Healthmentioning
confidence: 99%
“…Although other studies (in India and Brazil) have shown lower ascorbate concentrations in people with Parkinson’s disease compared to healthy controls [ 16 , 17 ], based on the low control values and the less than ideal analytical methodology used, it is possible that these low values were due to artifactual ex vivo oxidation [ 27 ]. Alternatively, individuals in low-middle income countries tend to have lower vitamin C status, and thus may be more prone to developing hypovitaminosis C during various disease states [ 32 , 33 ]. Of note, the Parkinson’s disease group in our study had a higher prevalence of hypovitaminosis C, where the subclinical symptoms of vitamin C deficiency start to become apparent [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of micronutrients may be affected by factors such as genotypes, the intake of other food components, disease status etc. [32] Future work should focus on determining the serum micronutrient status of the tuberculosis patients and its association with the cure rate.…”
Section: Discussionmentioning
confidence: 99%